2016
DOI: 10.4236/detection.2016.42005
|View full text |Cite
|
Sign up to set email alerts
|

Study the Attenuation Coefficient of Granite to Use It as Shields against Gamma Ray

Abstract: The present work investigates the linear and mass attenuation coefficients for gamma rays practically and theoretically by using spectroscopy gamma ray (UCS-20) and program (XCOM)) for various types of common use granite, and compares them with the lead because of its high blocking ability for this type of radiation. This paper concluded through linear and mass attenuation coefficients measurements that these coefficients decrease with increasing incident photons energy. Measurements also showed that the linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Hence, concrete, being far less toxic, is the first choice in the construction of walls and flooring of radiation facilities. Although other materials such as ceramic (brick) [4] and granite [5] have been tested for their usefulness as shielding materials, their linear attenuation coefficient µ is 0.08 to 0.13 cm −1 for the 60 Co gamma ray source, which is even lower than those of the various heavyweight concrete mixtures (0.15-0.19) [6]. Hence, radioprotective shields for medical radiation facilities such as linear accelerators and for industrial gamma ray sterilization systems are constructed of concrete or concrete with an inserted iron plate.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, concrete, being far less toxic, is the first choice in the construction of walls and flooring of radiation facilities. Although other materials such as ceramic (brick) [4] and granite [5] have been tested for their usefulness as shielding materials, their linear attenuation coefficient µ is 0.08 to 0.13 cm −1 for the 60 Co gamma ray source, which is even lower than those of the various heavyweight concrete mixtures (0.15-0.19) [6]. Hence, radioprotective shields for medical radiation facilities such as linear accelerators and for industrial gamma ray sterilization systems are constructed of concrete or concrete with an inserted iron plate.…”
Section: Introductionmentioning
confidence: 99%
“…The (µ/ρ) values are comparable for the three granites. Consequently, (µ) can provide clearer discrimination between granites, as a shielding material, than (µ/ρ), see also [9] and [14]. This can be correlated with the atomic numbers of the constituting atoms and the experimental set-up.…”
Section: The Linear and Mass Attenuation Coefficientsmentioning
confidence: 96%
“…[8] The linear and mass attenuation coefficients of gamma rays transmitted through granites of different countries were studied in the energy range 0.081-1.332 MeV. [9] It was concluded that the linear attenuation coefficients are appropriately correlated with the material density. Moreover, the mass attenuation coefficients are larger for materials of large atomic numbers.…”
Section: Introductionmentioning
confidence: 99%
“…al. (2016) [13], a Monte Carlo simulation was employed to determine a set of linear attenuation coefficient, as well as mass attenuation coefficient, for various types of granite used in the construction, using a gamma irradiation source. fields.…”
Section: Introductionmentioning
confidence: 99%